Buku sakti vocabulary : kosa-kata bahasa Inggris sehari-hari beserta contohnya /Ifa Laila A.R.; penyunting, Slamah - IFA LAILA A.R. , 1989-; Salamah (Pusat Kajian Bahasa, 2017)
220 hlm. : ilus. ; 20 cm